Sport psychology for young athletes - Knight, Camilla J.; Harwood, Chris; Gould, Daniel (Routledge, Taylor & Francis Group, 2018)
Understanding and applying psychology within youth sport settings is key to maximising young athletes' enjoyment, wellbeing, and sporting performance. With real-life case studies that demonstrate psychological theory put into practice, it discusses a wide spectrum of issues faced by young athletes and recommends the best approaches to addressing them. This book is the first to offer an evidence-based introduction to the theory and practice of sport psychology for children and young athletes.